Research on the influence of rotational speed on the performance of high-speed permanent-magnet generator - Hongbo Qiu; Yanqi Wei; Xi Fang Zhao; Cunxiang Yang; Ran Yi (Archives of Electrical Engineering, 2019)
When the machine is at high speed, serious problems occur, such as high frequency loss, difficult thermal management, and the rotor structural strength insufficiency. In this paper, the performances of two high-speed permanent magnet generators (HSP- MGs) with different rotational speeds and the same torque are compared and analyzed. The two-dimensional finite element model (FEM) of the 117 kW, 60 000 rpm HSPMG is established. By comparing a calculation result and test data, the accuracy of the model is verified. On this basis, the 40 kW, 20 000 rpm HSPMG is designed and the FEM is established. The relationship between the voltage regulation sensitivity and power factor of the two HSPMGs is determined. The influence mechanism of the voltage regulation sensitivity is further revealed. In addition, the air-gap flux density is decomposed by the Fourier transform principle, and the influence degree of different harmonic orders on the HSPMG performance is determined. The method to reduce the harmonic content is further proposed. Finally, the method to improve the HSPMG overload capacity is obtained by studying the maximum power. The research showed that the HSPMG at low speed (20 000 rpm) has high sensitivity of the voltage regulation, while the HSPMG at high speed (60 000 rpm) is superior to the HSPMG at low speed in reducing the harmonic content and increasing the overload capacity.